The Pathology of Bureaucracy in the Implementation of Poverty Alleviation Programs - Nurainy Latuconsina; Amir F. Kotaromalos; Joana J. Tuhumury (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This study investigates bureaucratic issues within poverty alleviation programs in Batumerah Village, Ambon City, using a qualitative phenomenological approach. The findings reveal that corruption, nepotism, and ineffective policy implementation severely undermine the success of these programs. Additionally, limited awareness and poor governance further exacerbate these problems. To address these challenges, comprehensive bureaucratic reform is essential, emphasizing transparency, accountability, public participation, and improved data management. Developing evidence-based policies and promoting long- term economic empowerment, including job training and financial support, are crucial for enhancing community well-being and ensuring the sustainability of poverty alleviation efforts.